Effect of Time, pH, and Yeast Concentration on Bioethanol Levels in the Ulva sp. Fermentation Process - Aina Christalia Rinastiti; Dianita Ivana Permata; Bekti Palupi; Zuhriah Mumtazah; Meta Fitri Rizkiana; Atiqa Rahmawati (University of Jember, 2022)
Bioethanol is a form of renewable energy used to reduce dependence on fossil fuels, which have various adverse environmental impacts. Ulva sp. contains high amounts of carbohydrates, which can potentially be a raw material for bioethanol production. This study aims to determine the optimal conditions of the fermentation process, considering the variables of time, pH, and yeast concentration. This study used the hydrolysis results of Ulva sp. with optimum operating conditions of 0.1 N HCl concentration, 80 mesh particle size, and 450-watt microwave power. Measurement of bioethanol levels was performed using an alcohol meter. The results showed that the optimal conditions for fermentation were 7 days, pH 5.5, and a yeast concentration of 1.5%, resulting in a bioethanol content of 7.55%.